IDENTIFIKASI SENYAWA METABOLIT SEKUNDER PADA HASIL FRAKSINASI EKSTRAK Phaseolus vulgaris L. DENGAN METODE GAS CHROMATOGRAPHY-MASS SPECTROSCOPY (GC-MS) - Khurriyatul Khair; Yayuk Andayani; Aliefman Hakim (Postgraduate, University of Mataram, 2017)
This research was aimed to identify some classes of secondary metabolite compound on the fractionation results of green bean extract (P. vulgaris L.) using Gas Chromatography-Mass Spectroscopy (GC-MS) method. Green bean was extracted by methanol solvent. Fractionation of methanol extract used Vacuum Liquid Chromatography (VLC) with some variation of eluents such as n-hexane 100%; n-hexane: ethyl acetate (9 : 1 to 1 : 9); and ethyl acetate 100%, produced 11 major fractions. Based on Thin Layer Chromatography (TLC) analysis using DCM: MeOH (9.5: 0.5) as mobile phases, these 11 major fractions were classified based on their polarity such as non-polar, semi-polar and polar fraction. The results of identification by GC-MS spectrometer showed the presence of secondary metabolites such as monoterpenes in non-polar fraction; in semi-polar fraction was found terpenoids and steroids; in polar fraction was found monoterpenes, phenolic and steroid as the lowest percent area, that is less than 2%. Keyword: P.vulgaris L extract, fractionation, VLC, GC-MS